The influence of motivation and employee satisfaction on employee performance through organizational citizenship behavior at PDAM Giri Tirta Gresik district - Mersiana Varia Juita (Junal Ilmu Manajemen, 2023)
Performance is the achievement of work (performance) both in quantity and quality achieved by a person during a certain period usually in one year. Employees who complete their duties properly and correctly will have high performance. This study aims to test and analyze employee motivation and satisfaction on employee performance with Organizational citizenship behavior as an intervening variable. This research was obtained from labor respondents at PDAM Giri Tirta Gresik Regency totaling 769 respondents. Determination of the number of samples using a representative sample so as to get as many as 100 labor respondents. This study uses primary data, namely by distributing questionnaires. In addition to primary data, this study also uses secondary data. This type of research uses quantitative research. The data analysis technique used is Partial Least Square (PLS).The results of this study explain that 1) Motivation can contribute to improving Organizational citizenship behavior. 2) Employee satisfaction can contribute to improving organizational citizenship behavior. 3) Employee satisfaction can contribute to improving employee performance. 4) Employee satisfaction can contribute to improving employee performance. 5) Organizational citizenship behavior can contribute to improving employee performance. 6) Motivation can contribute to improving employee performance through organizational citizenship behavior. 7) Employee satisfaction can contribute to improving employee performance through organizational citizenship behavior.